Utilization of Information Technology as Media for Village Community Aspirations (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
The ease and openness of information is a necessity that demanded by society. Easy and fast access to information utilizing advances in information and communication technology can actually improve services to the community. Badan Permusyawaratan Desa (BPD) Saentis dan Kolam Kecamatan Percut Sei Tuan for the embodiment of democracy in the implementation of the village government are expected to be able to optimally provide information services to the village community. Until now, information service activities have not utilized online media that can be accessed easily and quickly to explore, accommodate, and channel the aspirations of the village community. Therefore, we need a system in the form of an application that can be used by BPD to explore, collect, and channel the aspirations of village communities online. The method applied in developing this application is the User Centered Design method, which is a user-focused design. The next, the target achieved is the availability of a web-based media for channeling the aspirations of rural communities that can be used easily and quickly.